Relationship Between Behaviour and Lifestyle Patterns and The Risk of Hypertension: A Scoping Review - Fauziyah, Fauziyah; Padilah, Fitri Nur; Nurkhodijah, May; Aprillia, Ristha Eka; Arrafah, Riva Nur; Pitora, Tobi (Jurnal Ilmiah Ners Indonesia, 2025)
Hypertension is an increasingly common health problem worldwide and poses a significant risk for various cardiovascular conditions. To prevent an increase in the incidence and mortality rates, preventive measures are needed to identify the risks associated with hypertension. Behavioral and Lifestyle changes are the primary foundation in the prevention and treatment of hypertension. Changing behavior is a key factor that can influence the lifestyle of individuals with hypertension. This scoping review aims to examine the relationship between lifestyle patterns, behavior, and the risk of hypertension. A scoping review was conducted using a comprehensive literature search across PubMed, ScienceDirect, and Taylor & Francis, focusing on original studies involving human participants, Behavior and lifestyle outcomes reported, and studies published between 2020 and 2025. Article analysis uses the PRISMA-ScR Checklist. A total of 7 studies were analyzed. Findings show that Individuals who are obese or have other diseases (ex, diabetes mellitus) and do not adopt a healthy lifestyle have a higher risk of complications such as hypertension. Lifestyle patterns and Behaviors such as abstaining from smoking, limiting alcohol consumption, maintaining a balanced diet (DASH diet), and engaging in regular physical activity have consistently been associated with reduced risk of hypertension and cardiometabolic comorbidities. Patients who combine physical activity and a healthy lifestyle have a lower risk of death. The integration of lifestyle modifications (such as not smoking, exercising, maintaining sleep quality, and not consuming alcohol) with medication adherence helps in the sustainable management of hypertension.